'Happy' drug survival of adalimumab, etanercept and ustekinumab in psoriasis in daily practice care: results from the BioCAPTURE network. (3rd October 2014) - van den Reek, J.M.P.A.; Zweegers, J.; Kievit, W.; Otero, M.E.; van Lümig, P.P.M.; Driessen, R.J.B.; Ossenkoppele, P.M.; Njoo, M.D.; Mommers, J.M.; Koetsier, M.I.A.; Arnold, W.P.; Sybrandy‐Fleuren, B.A.M.; et al.
Summary: Background: Drug survival is a marker for treatment success. To date, no analyses relating dermatological quality‐of‐life measures to drug survival have been published. Objectives: (i) To describe 1‐year drug survival for adalimumab, etanercept and ustekinumab in a daily practice psoriasis cohort, and (ii) to introduce the concept of 'happy' drug survival, defined as Dermatology Life Quality Index (DLQI) ≤ 5 combined with being 'on drug' at a specific time point. Methods: Data were extracted from a prospective registry. Drug survival was analysed using Kaplan–Meier estimates. 'Happy' drug survival was calculated, with data split into 'happy' (DLQI ≤ 5) vs. 'unhappy' (DLQI > 5) at baseline and months 3, 6, 9 and 12. Results: 249 treatment episodes were included (101 adalimumab, 82 etanercept, 66 ustekinumab). The 1‐year drug survival rates for ustekinumab, adalimumab and etanercept were 85%, 74% and 68%, respectively. Ustekinumab showed a better confounder‐corrected drug survival vs. etanercept [hazard ratio (HR) 3·8, P  =   0·02] and a trend towards better survival vs. adalimumab (HR 2·3, P  =   0·1). At baseline, the majority ( n  =   115, 73%) was considered 'unhappy' and a minority 'happy' ( n  =   42, 27%) (ratio 'happy':'unhappy' was 1 : 2.7). The percentage of treatment episodes with 'happy' on‐drug patients increased to 79% after 1 year. Conclusions: Ustekinumab showed a better overall drug survival than etanercept, and a trend towards a better overall drug survival than adalimumab. After 1 year, patients reported to be 'happy' in 79% of episodes and 'unhappy' in 21%. We introduced the new concept of 'happy' drug survival because the proportion of on‐drug patients with good quality of life is an important indicator for treatment success. Abstract : What's already known about this topic? The Dermatology Life Quality Index is a validated score for dermatology‐specific quality‐of‐life measurements. Drug survival studies of biologics for psoriasis show varying results and differ in study design and population. To date, studies including drug survival rates for ustekinumab are scarce. What does this study add? The introduction of a concept named 'happy' drug survival, which combines drug survival rates with dermatology‐specific quality‐of‐life measures to evaluate treatments for psoriasis. Analysis of 'happy' drug survival showed that the proportion of 'on‐drug' biologic users with a good quality of life increased from 27% to 79% after 1 year of treatment. Ustekinumab showed a better overall drug survival vs. etanercept and a trend towards a better survival vs. adalimumab.